2009
DOI: 10.1590/s0103-84782009000500012
|View full text |Cite
|
Sign up to set email alerts
|

Método de comparação de modelos de regressão não-lineares em bananeiras

Abstract: Método de comparação de modelos de regressão não-lineares em bananeiras Method of comparison of models non-linear regression in bananas trees

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
1
13
0
8
Order By: Relevance
“…measures the adherence of the estimated data to the obtained data (Maia et al, 2009). The calculations were performed with the help of Microsoft Office Excel® application and software statistic R (R Development Core Team, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…measures the adherence of the estimated data to the obtained data (Maia et al, 2009). The calculations were performed with the help of Microsoft Office Excel® application and software statistic R (R Development Core Team, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, nonlinear growth models such as the Spillman, Mitscherlich, logistic (Verhulst), Gompertz, and Richards, among others (REGAZZI, 2003), are advantageous when compared to linear models because they more accurately predict plant growth. Among these, the logistic growth model has been considered the most suitable in recent studies on plant growth (MAIA et al, 2009;PUIATTI et al, 2013;PRADO et al, 2013). Growth predictions for China pinks in different substrates prior to flowering are important for planning commercial production because they will allow growers to estimate distribution dates and calculate when to start production.…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was reported by Puiatti et al (2013), who identified and grouped the nonlinear regression models that best fitted the description of the total dry matter accumulation of garlic plant over time, where L showed better performance than that of the B, G, L, M, M1, M2, vB, and Meloun III models. The L model fitted the data well in several experiments with nonlinear regression models, for the description of growth curves or nutrient accumulation, as in Pôrto et al (2007) for onion cultivation, Maia et al (2009) for banana trees, and Martins Filho et al (2008) who also reported great adjustments for the L model using the Bayesian methodology for the growth data of two bean cultivars.…”
Section: Resultsmentioning
confidence: 86%